Pemberdayaan Caregiver melalui Program “CITRA: Caregiver Inovatif untuk Lansia” Berbasis Aplikasi sebagai Upaya Peningkatan Kualitas Hidup Lansia di Surabaya - Ferry Efendi; Retno Indarwati; Rifky Octavia Pradipta; Visky Afrina; Faisal Adi Irawan (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2026)
Introduction: The growing elderly population in Indonesia raises health challenges, including chronic diseases and cognitive decline. Informal caregivers play a key role, yet limited knowledge and digital literacy reduce care quality. Method: The CITRA (Innovative Caregiver for the Elderly) program was conducted from July to September 2025 in Pacar Kembang, Surabaya. Twenty informal caregivers participated in health education, Android-based CITRA app training, and door-to-door mentoring. Evaluation used pre- and post-tests analyzed with the Wilcoxon test. Results: Caregivers’ knowledge improved significantly. In the first session, scores rose from 65 ± 10.13 to 82.75 ± 6.58 (p=0.000). In the second, scores increased from 71.5 ± 9.44 to 87.5 ± 8.57 (p=0.005). Skills in basic health checks and app utilization also improved. The CITRA app served as an accessible educational tool, though currently limited to Android devices. Discussion: Capacity improvement supports the active ageing framework and aligns with evidence that technology-based interventions effectively empower families in elderly care. Conclusion: CITRA successfully enhanced caregiver knowledge, skills, and provided a replicable digital innovation to improve elderly quality of life in Indonesia.